The role of digital technology in supporting public services in Indonesia - Haedar, Ahmad Wahidiyat (PINISI Discretion Review, 2023)
This study explores the transformative impact of digital technology on public services in Indonesia, a country with a diverse and rapidly evolving socio-economic landscape. The primary objective is to analyze how digital tools and platforms are being integrated into public service delivery, thereby enhancing efficiency, accessibility, and user satisfaction. Adopting a qualitative research methodology, the study involved in-depth interviews with key stakeholders, including government officials, technology experts, and end-users of public services. Additionally, case studies of successful digital initiatives in various Indonesian regions were examined to understand the practical implications of digital integration. The findings reveal significant improvements in public service delivery, characterized by streamlined processes, reduced bureaucracy, and increased transparency. The research highlights the pivotal role of government policies in facilitating this digital transformation, alongside challenges such as digital literacy and infrastructure disparities. The study concludes with recommendations for future digital strategies in Indonesia's public sector, emphasizing the need for inclusive and sustainable approaches to harness the full potential of digital technology in public service delivery.